Acoustic-mechanical and microscopic investigation of corundum material - RANACHOWSKI, Przemysław; REJMUND, Feliks; PAWEŁEK, Andrzej; PIĄTKOWSKI, Andrzej (Archives of Acoustics, 2007)
This paper presents the results of acoustic emission (AE) measurements of samples under compressive stress. Additional research, concerning structure and parameters of the material, were performed using microscopic and ultrasonic methods. The object of investigation were samples of corundum material C 799 type. The content of alumina in investigated material was equal to 99.7%. The corundum materials demonstrate high mechanical, thermomechanical as well as grindability resistance and find wide application in production of modern technical devices. The aim of study was recognition of stages of degradation processes of the corundum structure. The analysis of AE results pointed out diversified strength and mechanical-acoustic characteristics of particular samples. It was stated during microscopic investigation that the main reason for this effect is due to different grains size and their spatial distribution. The authors consider the abnormal grain growth (AGG) phenomenon as a reason of inhomogeneities of the corundum structures in particular samples. This effect occurs at longer sintering term, especially for fast temperature growth. AGG phenomenon has random character and up to now is not explained in satisfying way.